Saving and investment in a two-sector model of endogenous growth of a small open economy - Cásares, Enrique R. (Estudios Económicos de El Colegio de México, 1998)
We develop a two-sector model of endogenous growth. The export sector is the only sector that generates technological progress. Technological knowledge can be used by the; import sector. Firms face adjustment costs for investment. The model has well-defined equations for the growth rate of capital, and for the growth rate of consumption. The model has a steady-state solution. We study the relation between the interest rate and the growth rate. The optimal growth rate is higher than that achieved in the market economy without government. The optimal policy is an investment subsidy in the export sector.